Management of Organizing Arabic Debate Training for The Student Organization “El-Jidal Reborn” to Improve Speaking Skills - Imroatul Ngarifah; Siti Maisaroh; Zakiyah Arifa (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Abstract Purpose - This research purposes to know the functions of El-Jidal Reborn management for Arabic debate training organizing for organizing speaking skills. Design/methodology/approach - The research is descriptive field research. The primary data sources are obtained from interviews with the organization's supervisor, leader, minister, and coordinator. Findings/result - The results of this study are the organizing to achieve better implementation of debate training for improving their speaking skill that preparing the training schedule for the debate. They also recorded the training process as an instrument of evaluation. Originality/value - in managing the organization, strengthens solidarity and synergy between ministries so that the functions create interesting and interactive debate training. So that students' speaking skills can be improved. Paper type - Research paper